Informasi COVID-19 Dapat Meningkatkan Perilaku Hand Hygiene Pada Tenaga Non Kesehatan di Masa Pandemi COVID-19: Information of COVID-19 can improve Hand Hygiene Behavior in Non-Health Workers during the COVID-19 Pandemic - Nurhayati; Tresya, Elvie; Suryadi, Bambang (Dohara POAJ, 2022)
Introduction: Health workers and non-health workers play a role in providing services and determining the prevention of COVID-19 transmission in hospitals so that they are at high risk for exposure and infection. Therefore it is necessary to prevent it with hand hygiene. Methods: This study uses a quantitative method with a crossectional research design, used 89 respondents. The instrument used was a questionnaire on the level of knowledge of COVID-19 information and Hand Hygiene Behavior made by the researcher. Results: From the univariate data, it was found that most of the respondents had sufficient knowledge of COVID-19 information, namely 48 out of 89 respondents (53.9%), and most of them had negative Hand Hygiene behavior, namely 52 out of 89 respondents (58.4%). From the results of the bivariate test, it was found that there was a relationship between the Level of Knowledge of COVID-19 Information and Hand Hygiene Behavior with a p-Value of 0.003 (p<0.05). Discussion: Knowledge of COVID-19 information can improve hand hygiene behavior for non-health workers in hospitals. Non-health workers can improve hand hygiene behavior to prevent the spread of the COVID-19 virus during the pandemic by continuing to upgrade knowledge about COVID-19 itself.